Study of communication ethnography for entrepreneurship culture in the interpersonal relations of teachers and students - Triwardhani, Ike Junita; Trigartanti, Wulan; Putra, Raditya Pratama (Penerbit Universiti Kebangsaan Malaysia, 2020)
Entrepreneurship is an important issue in the era of intense competition because it involves how businesses always build new ideas that add value and are knowledge-based and the emergence of innovations. The actors in the school are teachers, students, parents of students and the surrounding community build that entrepreneurship culture, those which are driven through teacher and student relations. The purpose of this paper is to map the relationships built between teachers and students, how teachers built credibility on these relationships, how the motivation was conveyed by the teacher, and map the entrepreneurial culture built up at the school. The method used was communication ethnography to track and map the interpersonal relationships of teachers and students in entrepreneurial learning in the cases studied. The research case chosen was primary schools which had the concept of a natural school, where entrepreneurship was an important part of learning. The entrepreneurship culture was developed by teachers and students as the main actors and supported by other important actors, namely parents and the community around the school. These actors built a culture of entrepreneurship. Relationships that were built between teachers and students through interpersonal communication would explain the culture of entrepreneurship built in schools. The culture of entrepreneurship in schools was built through the contribution of effective communication to the key actors involved, namely teachers, students, parents, and the surrounding community. The main driving force was the relationship between teachers and students built through interpersonal communication.